2018
DOI: 10.1099/jgv.0.001092
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid substitution in the NS4B protein of Dengue virus confers enhanced virus growth and fitness in human cells in vitro through IFN-dependent host response

Abstract: Dengue virus (DENV) replication between mosquito and human hosts is hypothesized to be associated with viral determinants that interact in a differential manner between hosts. However, the understanding of inter-host viral determinants that drive DENV replication and growth between hosts is limited. Through the use of clinical isolates, we identified an amino acid variation of Ala, Met and Val at position 116 of DENV-1 NS4B. While the proportion of virus with the NS4B-116V variant remained constantly high in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Image processing and base calling were generated as FASTQ files. Quality assessment was performed using the Miseq control software, in which samples with a Q score of >30 were used for further analyses (20). Phylogenetic analyses and molecular dating: Low-quality sequences were removed by FASTX-Toolkit Ver 0.0.14 (21) from the input data file.…”
Section: )mentioning
confidence: 99%
“…Image processing and base calling were generated as FASTQ files. Quality assessment was performed using the Miseq control software, in which samples with a Q score of >30 were used for further analyses (20). Phylogenetic analyses and molecular dating: Low-quality sequences were removed by FASTX-Toolkit Ver 0.0.14 (21) from the input data file.…”
Section: )mentioning
confidence: 99%
“…For example, ZIKV antagonizes interferon-β (IFN-β) induction via an evolutionary NS1 mutation, thereby promoting replication efficiency in mosquitoes and enhancing neurovirulence in mammals[ 26 ]. A single amino acid substitution in NS4B of DENV enhances virus growth and fitness in human cells in vitro through an IFN-dependent host response[ 27 ]. For JEV, the replication efficiency and virulence positively correlate with the ability to inhibit the IFN-I mediated antiviral response[ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Robinson et al (2018) also showed that the failure to induce IFI44L contributed to the long-term propagation of ZIKV in germ cells. The expression of ISGs, including IFI44L, OAS1, and IFIT3, was downregulated by the NS4B protein of dengue virus (DENV) in human cells and thus resulted in high viral replication, which was an immune evasion strategy for DENV (Bui et al, 2018). In this study, a series of ISGs were increased in RIPK3 −/− mouse brains after JEV infection, among which IFI44L was increased most significantly compared with that in the WT.…”
Section: Discussionmentioning
confidence: 77%